Rain-light sensor for automated windshield wiper system - Anuar, Asyran (Penerbit UTHM, 2017)
Nowadays, transportation is an important things needed by everyone. Car is one of the transportation that commonly used by many people. The fact that car is commonly used by the people because it is convenient in terms of weather exposure and comfort issue. Car has been improved year by year in technological aspect. Many inventors competes each other in order to propose their invention to be applied in car technology. One of the best inventions that had been applied is automated windshield wiper system. Automated windshield wiper used a sensor called rain-light sensor to control car’s wiper based on the driving weather condition.